PENGARUH KONFLIK PERAN GANDA DAN STRES KERJA TERHADAP KINERJA MOMPRENEUR (WIRAUSAHA WANITA) DI KECAMATAN CIBUNGBULANG - Dini Nurfadillah; Rita Yuni Mulyanti; Nurtiah Nurtiah (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The purpose of this study was to analyze several variables that could influence the performance of mompreneurs (women entrepreneurs) in Cibungbulang District. As for the variables in this study are multiple role conflicts, job stress and performance. This research was conducted using primary data obtained from questionnaires filled out by 83 respondents in Cibungbulang District. The analytical method used is multiple linear regression analysis. The results of this study indicate that multiple role conflicts have a negative and significant effect on performance, while job stress has a negative and insignificant effect on performance. The conclusion in this study is that multiple roles conflict and work stress simultaneously have a significant effect on the performance of mompreneurs (women entrepreneurs) in Cibungbulang District. The implications of this research for mompreneurs (women entrepreneurs) can pay attention to role conflicts regarding the division of time between business and family activities, so that they do not interfere with these two activities so that balance can be achieved, what can be done is to make a work schedule for business activities and homework. stairs. Key words: multiple role conflict, job stress, performance.